STUDI KOMPARATIF KINERJA KEUANGAN METODE CAMEL PADA PT. BANK MANDIRI Tbk. dan PT. BANK CENTRAL ASIA Tbk. - Nanda Sabra Qadrullah; Yuliani Yuliani; H.M. Rasyid Umrie (Politeknik Negeri Sriwijaya, 2015)
This research aimed to analyze the financial performance and level of health of banks by using CAMEL analysis through financial statements of PT Bank Mandiri, Tbk and PT Bank Central Asia, Tbk from 2008 to 2012. This research is descriptive and comparative in both of the banks. The result shows that overall PT Bank Central Asia Tbk is healthier than PT Bank Mandiri, Tbk. PT Bank Central Asia, Tbk is healthier in the aspect of Asset, Management, Earning, and Liquidity than PT Bank Mandiri, Tbk. Meanwhile, PT Bank Mandiri, Tbk is healthier than PT Bank Central Asia, Tbk on just the Capital’s aspect.